Juridical Review of Employment Agreements for Fixed and Indefinite Times from a UU Perspective No. 13 Year 2003 and UU Cipta Kerja (Case Study of the Verdict No.181/Pdt.Sus-Phi/2020/Pn.Mdn) - Herman Brahmana; Monica Cita Laras Samosir; Dina Ariani L. Tobing; Joyce Shania Silaban (IHSA Institute, 2024)
There are two types of employment agreement formation, namely PKWTT and PKWT. However, in its application, PKWT by companies has several things that are contrary to the regulations in the Employment Law and work agreements, therefore regulations related to employment are still hampered by various problems, obstacles and challenges that need to be faced and require a resolution process through the courts. In this case, normative juridical research methods are used in this research. Primary, secondary and tertiary legal materials are used as research legal materials. The employment relationship between employers and workers is based on a work agreement which is based on Law Number 13 of 2003 concerning Employment and the Job Creation Law